Variable thermal conductivity in micropolar thermoelastic medium without energy dissipation possessing cubic symmetry - Ailawalia, Praveen; Priyanka, S. (Zielona Góra: Uniwersytet Zielonogórski)
This investigation deals with the effect of variable thermal conductivity in a micropolar thermoelastic medium without energy dissipation with cubic symmetry. The normal mode technique is employed for obtaining components of physical quantities such as displacement, stress, temperature distribution and microrotation.
Keywords: variable thermal conductivity; microrotation; temperature distribution; normal mode analysis